Extratropical low-frequency variability in a three-level quasi-geostrophic atmospheric model with different spectral resolution - Weisheimer, A; Kurgansky, M; Dethloff, K; Handorf, DR (2003)
Apart from variations of external forcing components and interactions between climate subsystems, natural atmospheric fluctuations with periods of years, decades and centuries can also be generated by inherent atmospheric dynamical instabilities of the flow. The objective of this study is to investigate the spatial and temporal structure of internal low-frequency atmospheric variability of the Northern Hemisphere using a minimum-complexity model of the extratropical circulation. Here, the main focus is the influence of varying spectral horizontal resolution on the formation of dominant patterns of variability. For this purpose, a three-level quasi-geostrophic atmospheric model with idealized thermal and orographic forcing has been integrated over 1,000 years under perpetual winter conditions with T5, T10, T15, and T21 resolutions. It has been shown that for the crude resolution T5 a rather strong bias occurs, whereas starting with T1O resolution, the nonlinear feedback between large- and small-scale features is reasonably well described. At this resolution a sort of plateau in the model performance has been reached, in respect to both the model climatology and the spatiotemporal structure of variability. Ultralow-frequency variability is most pronounced in the model's stratosphere and is associated with changes in the polar vortex strength and shape caused by vertically propagating planetary waves. Rossby wave trains in the lee of the model large-scale orography are the most dominant structures of long-period fluctuations in the middle troposphere. The results show that interannual- and decadal-scale variations can, in substantial part, be considered as a manifestation of the natural variability of the extratropical atmosphere. The inclusion of a seasonal cycle of the model's diabatic heating increases the interannual and interdecadal variability.